2019
DOI: 10.1111/imj.14160
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of oncology unit patients requiring admission to an Australian intensive care unit

Abstract: Background Patients with advanced malignancies have historically been considered poor candidates for admission to the intensive care unit (ICU); however, prognosis is continually improving, and requirements for ICU access are increasing. Aim To understand the characteristics and outcomes of oncology unit patients admitted to an Australian ICU and identify potential prognostic factors. Methods A single‐centre, retrospective, cohort study conducted at a tertiary public hospital with a quaternary ICU in Sydney, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Oncologists also need to recognize that patients with metastatic solid organ malignancies have poor survival outcomes after intensive care unit admission, with studies defining predictors as lung cancer (although in the preimmunotherapy era), extent of systemic disease, need for invasive mechanical ventilation, or renal replacement therapy or vasopressor support. [33][34][35][36] The COVID-19 pandemic is unprecedented in our lifetime, and we are likely to have to make difficult and distressing decisions. It is incumbent on us as an oncology community Port flushes can be reduced to every 8-10 weeks in situations of resource limitation.…”
Section: Vaccinationsmentioning
confidence: 99%
“…Oncologists also need to recognize that patients with metastatic solid organ malignancies have poor survival outcomes after intensive care unit admission, with studies defining predictors as lung cancer (although in the preimmunotherapy era), extent of systemic disease, need for invasive mechanical ventilation, or renal replacement therapy or vasopressor support. [33][34][35][36] The COVID-19 pandemic is unprecedented in our lifetime, and we are likely to have to make difficult and distressing decisions. It is incumbent on us as an oncology community Port flushes can be reduced to every 8-10 weeks in situations of resource limitation.…”
Section: Vaccinationsmentioning
confidence: 99%
“… 9 Other single-center studies have reported lower hospital mortalities than in our study (22, 29.8, and 31%, respectively). 10 12 The hospital mortality rates vary widely based on inclusion and exclusion criteria, with wide regional differences in epidemiology of cancers and their management. A systematic review published by Puxty et al, which included 31 studies with nearly 75,000 patients, reported an average hospital mortality of 38.2% (33.8–42.7%), with a range of 4.6–76.8%.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other studies, which had relatively higher proportion (33–76%) of such patients. 10 , 11 , 17 , 18 To the best of our knowledge, only two studies from Asia 9 , 12 have reported outcomes in this subset of patients. However, these reports did not record whether the presence of distant metastasis was a predictor of mortality or not.…”
Section: Discussionmentioning
confidence: 99%
“…7 Advanced age 10 does not prevent ICU admission, nor does malignancy. 11,12 Australian and New Zealand ICU practice has made notable contributions both to the development of the concept of a hospital Medical Emergency Team (MET) and Rapid Response Team (RRT) and to the early widespread adoption of this concept, 13 where a team of clinicians, typically ICU-based, provide a safety net for potentially deteriorating patients outside the ICU. The clinical utility of such a hospital rapid response to at-risk patients outside the ICU seemed from the beginning to be self-evident.…”
Section: Jeffrey Presneillmentioning
confidence: 99%